Tinjauan Kritis Terhadap Ontologi Sains Modern (Hakikat Realitas, Tafsir Metafisika, dan Asumsi Dasar Ilmu) - Muhammad Aditya Firdaus; Nanat Fatah Natsir; Erni Haryanti (Jurnal Ilmiah Wahana Pendidikan, 2021)
The presence of modern science originated from developments between the ages or can also be called the form of the renaissance. The presence of modern science as modernism has received a lot of criticism from several post-modern philosophers and even traditionalist philosophers, one of which is Sayyed Hossein Nasr. According to Nasr's view, the root of all crises in the modern world is the misconception of human beings in which the modern world separates science and religion. The purpose of this paper is to explore some critical reviews of the ontology of modern science using the literature study method. The results of the study show that modern science has reduced many things in human life, and has brought emptiness and meaninglessness of life for humans. Metaphysical interpretation is concerned with what is captured by the mind, including the sensing of all human experience, is mental. Everything boils down to science which has the characteristics of systematic knowledge based on sensory observations or 'systematic knowledge of nature and the physical world.